Remarkable Site Specificity of Local Transposition Into the Hsp70 Promoter of Drosophila melanogaster - Shilova, Victoria Y. (Copyright © 2006 by the Genetics Society of America, 2006)
Heat-shock genes have numerous features that ought to predispose them to insertional mutagenesis via transposition. To elucidate the evolvability of heat-shock genes via transposition, we have exploited a local transposition technique and Drosophila melanogaster strains with EPgy2 insertions near the Hsp70 gene cluster at 87A7 to produce numerous novel EPgy2 insertions into these Hsp70 genes. More than 50% of 45 independent insertions were made into two adjacent nucleotides in the proximal promoter at positions −96 and −97, and no insertions were into a coding or 3′-flanking sequence. All inserted transposons were in inverse orientation to the starting transposon. The frequent insertion into nucleotides −96 and −97 is consistent with the DNase hypersensitivity, absence of nucleosomes, flanking GAGA-factor-binding sites, and nucleotide sequence of this region. These experimental insertions recapitulated many of the phenotypes of natural transposition into Hsp70: reduced mRNA expression, less Hsp70 protein, and decreased inducible thermotolerance. The results suggest that the distinctive features of heat-shock promoters, which underlie the massive and rapid expression of heat-shock genes upon heat shock, also are a source of evolutionary variation on which natural selection can act.